The Concept of the Meeting Point of Hisab and Rukyat of the Beginning of the Hijri Month - Sakirman, Sakirman; Jamil, A (Nizham Jurnal Studi Keislaman, 2024)
The determination of the beginning of the lunar month still leaves debates in various criteria used by the hisab and rukyat methods. The debate leads to differences in starting and ending the beginning of the lunar month which is loaded with the implementation of worship. Conceptually, both hisab and rukyat can be analogized in a side of the coin. Both will not conflict if studied with the correct methodology. The debate on the criteria in the hishab and rukyat methods that occurs on the surface is due to grassroots friction that does not understand the two methods. This study examines how